Answer:
Step-by-step explanation:
Given is a function as
[tex]y=f(x)=x^2+x[/tex]
two values of x are x=-1 and x=2
Corresponding y values are
y(-1) = 1-1 =0 and
y(2) = 4+2 =6
Hence the two points are (-1,0) and (2,6)
Secant line equation can be obtained using two point formula for straight lines
a) Secant line joining (-1,0) and (2,6) is
[tex]\frac{y-0}{6-0} =\frac{x+1}{2+1} \\y = 2x+2[/tex]\
is the equation of the secant line
b) to find equation of tangent line
Slope of tangent line at (-1,0) = value of derivative at that point
[tex]y' = 2x+1\\y'(-1) = -2+1=-1[/tex]
So m =-1 and one point on the line is point of contact (-1,0)
So using point slope formula
[tex]y-0=-1(x+1)\\y = -x-1[/tex]